New technique of seeding chondrocytes into microporous poly(L-lactide-co-epsilon-caprolactone) sponge by cyclic compression force - Induced suction - Xie, Jun; Jung, Youngmee; Kim, Soo Hyun; Kim, Young Ha; Matsuda, Takehisa (MARY ANN LIEBERT INC, 2006)
The initial requirement for a functional engineered cartilage tissue is the effective and reproducible seeding of chondrocytes into the interior of microporous scaffolds. High seeding efficiency, high cell viability, uniform cell distribution, and short operation time are also essential. We devised a new technique of seeding rabbit chondrocytes into microporous poly(L-lactide-co-epsilon-caprolactone) (PLCL) (porosity, 71-80%; wall thickness, 2 and 6 mm) sponges under compression force-induced suction using a custom-designed loading apparatus. Cell distribution and cell viability were determined using confocal laser scanning microscopy with fluorescent dye-staining techniques. Factors that affect the quality of a cell-seeded construct were studied, namely, the porosity and thickness of sponges and suction cycles. Under 1 cycle of suction, an increase in porosity promoted cell seeding efficiency (CSE; defined as the percentage of the number of cells in the sponges relative to the initial number of cells seeded), cell viability (at 1 day postseeding), and a relatively uniform cell distribution, whereas thick sponges exhibited an inhomogeneous cell distribution irrespective of incubation time. Multiple cycles of suction of 5 and 10 at 0.1 Hz significantly improved the CSE, whereas high cell viability was maintained and even spatial cell distribution was achieved in 1 week. This study revealed that our newly developed cell seeding technique with multiple cycles of suction is a promising approach to inoculating cells into microporous sponges with high CSE, high cell viability, and homogeneous cell distribution.
Keywords: EPSILON-CAPROLACTONE; BIOREACTOR SYSTEM; PLCL SCAFFOLDS; L-LACTIDE; TISSUE; CARTILAGE; CULTURE; REGENERATION; COPOLYMERS; MORPHOLOGY